A study on production productivity improvement in food processing industries - Siti Nor, Ya (2013)
Small and Medium Enterprises (SMEs) have always played a key role in the economies of all major industrial societies in both of productivity and employment level. At the same time, most of the new manufacturing concepts and technologies have been implemented in a large scale of the improvement. However, SMEs especially in the small company in food processing industries have not attention for the improvement of such new manufacturing concepts and technologies with the objectives to improve productivity. This study focuses on productivity improvement effort for processing industry in one of SMEs Company with food frozen process. An attempt has been made in this paper to present some of the implementing based on brainstorming concept of productivity improvement in food processing industries. This research has taken place in Kota Bharu, Kelantan located in industry area. The objective of the research are to identify reason for low productivity level of production in food processing industries and to propose methods to increase productivity level of production in food processing industries. Attempt to explain the effective of propose strategies improvement with the simple guidelines. In addition, this study uses interview and observation as a method for the collect data. From the observation method, the researcher find some of solution for kind of problem in this company. Lastly, the analysis results of this method use the brainstorming methods for the last step with approval or accepted this solution from discussion with manager and expert person.